2019
DOI: 10.1016/j.tws.2019.02.001
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical analysis of axially loaded circular high strength concrete-filled double steel tubular short columns

Abstract: Numerical analysis of axially loaded circular high strength concrete-filled double Numerical analysis of axially loaded circular high strength concrete-filled double steel tubular short columns steel tubular short columns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…Little research has been reported on the structural behavior of thin-walled CFDST square columns that are subjected to eccentric loads. This paper Most of the investigations on CFDST columns reported previously has focused on circular cross-section [1][2][3][4][5][6][7][8][9][10][11][12] and tests on short square CFDST columns consisting of an inner circular steel tube have been very limited [13][14][15][16]. Pei [13] performed tests to determine the structural performance of stub CFDST square columns under axial and eccentric loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little research has been reported on the structural behavior of thin-walled CFDST square columns that are subjected to eccentric loads. This paper Most of the investigations on CFDST columns reported previously has focused on circular cross-section [1][2][3][4][5][6][7][8][9][10][11][12] and tests on short square CFDST columns consisting of an inner circular steel tube have been very limited [13][14][15][16]. Pei [13] performed tests to determine the structural performance of stub CFDST square columns under axial and eccentric loads.…”
Section: Introductionmentioning
confidence: 99%
“…c  and c  represent the longitudinal concrete compressive stress and corresponding strain, respectively; ' cc f and ' cc  the compressive strength and corresponding strain of confinedconcrete, respectively; c E the concrete elastic modulus[12], which is taken as 4400 reduction factor given by Liang[33], which considers the column size effect on the concrete compressive strength, and c D is taken as   strength as well as its corresponding strain of the core-…”
mentioning
confidence: 99%
“…The stress-strain relationships suggested by Liang [34] are used to simulate the ascending branch while the descending branch is described by the equations proposed by Lim and Ozbakkaloglu [44]. The descending parabolic branch of the stress-strain curve is determined by the following expression given by Lim and Ozbakkaloglu [44] ) ( (14) in which rp f denotes the lateral pressure applied by the steel tube on the concrete.…”
Section: Constitutive Laws Of Concretementioning
confidence: 99%
“…These studies showed that the core concrete was confined by both the inner and outer circular steel tubes, which increased both the ductility and capacity of circular CFDST columns. Ahmed et al [14] proposed confinement models for the core concrete in short CFDST circular columns based on available test results while the confinement model presented by Hu et al [15] was adopted to compute the maximum compressive strength of the concrete between the two tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Previously researchers studied the performance of CFDST short columns with various cross-sections [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The circular hollow tube (CHS) used for both outer and inner tubes in CFDST columns provides the most effective confinement to the core concrete compared to the other possible cross-sections.…”
Section: Introductionmentioning
confidence: 99%